Factors associated with low birthweight in North Shewa zone, Central Ethiopia: case-control study - Berhanu Gizaw; Samson Gebremedhin (BMC, 2018)
Abstract Background Low birthweight (LBW) is an important predictor of neonatal and post neonatal child morality. Though its risk factors have been extensively studied in the developed world; limited epidemiological evidence is available in developing countries including Ethiopia. The purpose of the study is to determine the risk factors of LBW in North Shewa zone, Central Ethiopia. Methods Unmatched case-control study involving 94 cases and 376 controls was conducted from Jan to Mar 2017 in three public hospitals in the zone. A case was defined as a singleton live birth with birthweight less than 2.5 kg; whereas, a control was a newborn that weighs 2.5-4.0 kg. Cases and controls were recruited on an ongoing basis until the required sample sizes were fulfilled. Data were collected by interviewing mothers, reviewing medical records and measuring the anthropometry of the mothers and the newborns. Bivariable and multivariable logistic regression analyses were used to identify risk factors of LBW. The outputs of the analyses are presented using adjusted odds ratio (AOR) with the respective 95% confidence interval (CI). Results Mothers with no formal education had two times increased odds of delivering LBW babies than women with formal education [AOR = 2.20 (95% CI: 1.11, 4.38)]. Mothers with no history of nutrition counseling during pregnancy had three times increased odds of giving LBW babies than those who were counseled [AOR = 3.35 (95% CI: 1.19, 9.43)]. Non-married women had higher odds of giving LBW newborns as compared to married ones [AOR = 3.54 (95% CI: 1.83, 6.83)]. Mothers from food insecure households had about four times higher odds of LBW as compared to food secure mothers [AOR = 4.42 (95% CI: 1.02,22.25)]. In contrast to mothers who had the recommended four or more antenatal care (ANC) visits, those who were not booked had three times increased odds of giving to LBW baby [AOR = 3.03 (95% CI: 1.19,7.69)]. Conclusion Improving the socio-economic status of mothers, enhancing the utilization of ANC and strengthening the integration of nutrition counseling into ANC help to reduce LBW.